Cyclophilin A as a biomarker for the therapeutic effect of balloon angioplasty in chronic thromboembolic pulmonary hypertension. Issue 4 (April 2020) - Kozu, Katsuya; Satoh, Kimio; Aoki, Tatsuo; Tatebe, Shunsuke; Miura, Masanobu; Yamamoto, Saori; Yaoita, Nobuhiro; Suzuki, Hideaki; Shimizu, Toru; Sato, Haruka; Konno, Ryo; Terui, Yosuke; et al.
Highlights: Plasma cyclophilin A (CyPA) levels were significantly elevated in chronic thromboembolic pulmonary hypertension. CyPA levels were linearly correlated with mean pulmonary arterial pressure and pulmonary vascular resistance. Balloon pulmonary angioplasty (BPA) reduced CyPA regardless of brain natriuretic peptide (BNP) at baseline. BPA decreased CyPA irrespective of the body mass index (BMI) at baseline. BPA did not lower BNP in patients with normal BNP or high BMI at baseline. Abstract: Background: Although cardiac troponin and natriuretic peptide have been shown to decrease after balloon pulmonary angioplasty (BPA) with improved right ventricular afterload in chronic thromboembolic pulmonary hypertension (CTEPH), biomarkers to evaluate the effects of BPA independently of heart failure status remain to be developed. Methods: In 39 consecutive CTEPH patients including 31 who underwent BPA, we measured plasma levels of cyclophilin A (CyPA), which we demonstrated is secreted from pulmonary vascular smooth muscle cells in response to mechanical stretch and hypoxia. Results: CyPA levels were elevated in CTEPH patients (12.7, IQR: 7.6-16.0) compared with 8 thromboembolic controls with a history of venous thromboembolism (4.9, IQR: 2.4-11.2) or 18 healthy controls (4.1, IQR: 2.4-6.8) (both p  <  0.05) and were linearly correlated with mean pulmonary arterial pressure ( r  = 0.50, p = 0.0003) and pulmonary vascular resistance ( r  = 0.32, p  =  0.026). BPA reduced CyPA levels and tended to lower brain-type natriuretic peptide (BNP) levels ( p  <  0.01 and p = 0.07). When comparing the changes in CyPA before and after BPA in the two subgroups with higher (≥35 pg/mL) and normal (<35 pg/mL) BNP at baseline, CyPA decreased both in patients with higher BNP and those with normal BNP (both p  <  0.05). In contrast, BNP decreased only in patients with higher BNP ( p  <  0.05). Also, CyPA decreased both in patients with lower (<25 kg/m 2 ) and higher (≥25 kg/m 2 ) body mass index (BMI) at baseline (both p  < 0.05), whereas BPA tended to reduce BNP in patients with lower BMI ( p = 0.12) but not in those with higher BMI ( p = 0.55). Conclusions: CyPA could be a useful biomarker to evaluate the effects of BPA even in patients with normal BNP or high BMI.